High Reliability and Fast-Speed Phase-Change Memory Based on Sb70Se30/SiO2 Multilayer Thin Films. (21st June 2018) - Zhang, Dan; Hu, Yifeng; You, Haipeng; Zhu, Xiaoqin; Sun, Yuemei; Zou, Hua; Zheng, Yan
Abstract : Sb70 Se30 /SiO2 multilayer thin films were applied to improve the thermal stability by RF magnetron sputtering on SiO2 /Si (100) substrates. The characteristics of Sb70 Se30 /SiO2 multilayer thin films were investigated in terms of crystallization temperature, ten years of data retention, and energy bandgap. It is observed that the crystallization temperature, 10-year data retention, and resistance of Sb70 Se30 /SiO2 multilayer composite thin films exhibited a higher value, suggesting that Sb70 Se30 /SiO2 multilayer composite thin films have superior thermal stability. The AFM measurement suggests that the SbSe (1 nm)/SiO (9 nm) multilayer thin films possess a smaller surface roughness (RMS = 0.23 nm). Besides, it was found that the phase-change time of SbSe (1 nm)/SiO (9 nm) multilayer thin films was shorter than that of GST in the process of crystallization and amorphization.